Formulasi Krim dan Analisa Potensi Antioksidan dari Fraksi Ekstrak Etanol Bawang Hitam - Firdausia, Rizqa Salsabila; Kurniawati, Endah; Rusydan, Azka Muhammad; Ardianto, Lisman Septa (MEDIA ILMU KESEHATAN, 2025)
Background: Reactive oxygen species (ROS) are free radicals that can cause damage to skin tissue. ROS can be prevented by antioxidants in plants that contain phenolics and flavonoids such as in black garlic. To obtain more specific compounds, fractionation of black garlic extract was carried out using polar, semi-polar and non-polar solvents. Objective: This study aims to determine the antioxidant activity by the FRAP method, then make and evaluate cream products from fractions of black garlic ethanol extract. Methods: Black garlic is made by heating garlic using a rice cooker, then extracted by maceration method. The resulting extract was fractionated with 3 solvents namely water, ethyl acetate and n-hexane. Furthermore, phytochemical screening and antioxidant analysis with the FRAP method were conducted. Fractions with the highest antioxidant activity were formulated into 3 cream preparations with extract concentrations of 0.5; 1; 1.5% and evaluated.Results: The water fraction had higher antioxidant ability, 1.545 ± 0.128 mmol/g extract. The water fraction was then developed into a cream preparation and evaluated the physical properties of the three formulas.Conclusion: Based on the test results, the three cream formulas have good physical properties and are stable at room and low temperatures.